MAJELIS ULAMA INDONESIA TENTANG “KHÂTAM” AL-NABIYYÎN (Studi atas Penggunaan Q.S. al-Azab, [33]:40 Sebagai Dasar Penetapan Fatwa Tentang Ahmadiyah) - Mohamad Yahya (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2011)
In this article the author elaborates upon the meaning of Khatam al-Nabiyyîn phrase.Phrase that becomes part of the Qur’an surah al-Ahzab, verse [33]: 40 are used as one ofbases for establishing the MUI fatwa about the deviate religious sect of Ahmadiyya. Thepurpose of writing this article is to consider proportionally over the use of the verse as abasis for establishing the fatwa. Proportional consideration is done by understanding theverse objectively. The method used in understanding the verse is FDE Schleiermacher’shermeneutic. In this hermeneutic, linguistic structure becomes into the beginning of reading before contextual reading of the verse reduction. From the dialectic of the two aspects of thereadings, objective meaning will be found. By using this method, the findings indicate that theMUI is less proportionate in using the verse as foundation of the fatwa. Khatam al-Nabiyyînis less appropriate if it is understood that Muhammad is the last prophet in a theologicalcontext. The phrase is more appropriate if it is understood that the Prophet Muhammad ismore special than other prophets.